An accurate ISF-based analysis and simulation method for phase noise in LC/Ring oscillators. (November 2021) - Jin, Zirui; Liu, Dongsheng; Hu, Ang; Shan, Xiaoyu; Zhang, Chengcheng; Su, Yanwen; Zou, Xuecheng; Zhao, Xu
Abstract: This paper presents an accurate ISF-based phase noise analysis method for LC/Ring oscillators. The proposed method can simultaneously quantify the effect of flicker noise and thermal noise on phase noise. The impulse sensitivity function (ISF) tool is used to evaluate the effect of flicker noise sources. An equivalent thermal noise resistor is utilized to assess the thermal noise contribution and simplify the analysis process. Based on the proposed method, the phase noise performance of a voltage-controlled oscillator (VCO) with source damping resistors is discussed. Simulated in 180-nm TSMC and 110-nm HHGRACE CMOS processes, the accuracy of the proposed method is verified. The predicted phase noise performance is consistent with the simulation results in 1/ f 3 and 1/ f 2 region, achieving 1-dB accuracy in diverse oscillator topologies.